Lightweight sound-insulation aerated concrete block and preparation method thereof

Through the use of modified polypropylene fibers and anti-aging agents, the problems of fibers prone to aging and poor dispersion in the prior art are solved, which significantly improves the sound absorption effect and sound insulation performance of aerated concrete and extends the service life.

CN119219390APending Publication Date: 2024-12-31NINGXIA MUERMA BUILDING MATERIAL
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411340767.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing sound-insulated aerated concrete blocks are prone to aging and not easily dispersed due to the untreated fibers, which leads to their sound absorption capacity not increasing but decreasing, which cannot effectively solve the problem of noise pollution.

Method used

Modified polypropylene fibers are used to modify the surface of silane coupling agent and a nanotitanium dioxide protective layer, combined with anti-aging agents to improve the antioxidant and dispersibility of the fibers, forming a similar fabric structure to enhance the acoustic characteristics.

Benefits of technology

It significantly improves the sound absorption effect of concrete, extends the service life of fibers, stabilizes the performance of cement mortar, and significantly improves the sound insulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059624590000091
    Figure BDA0005059624590000091
  • Figure BDA0005059624590000101
    Figure BDA0005059624590000101
Patent Text Reader

Abstract

The invention discloses a lightweight sound-insulation aerated concrete block and a preparation method thereof, and relates to the technical field of aerated concrete blocks. The polypropylene fibers are blended into the aerated concrete at a low mixing amount, so that the overall performance of the concrete is remarkably improved, the concrete is endowed with a new acoustic characteristic, and the polypropylene fibers have a unique physical property and a distribution mode; a structure similar to a natural or artificial fabric is formed in a pore network of the aerated concrete, when sound waves pass, tiny vibration of fibers can be induced, then the sound waves interact with surrounding pore walls, friction and energy conversion are generated, mechanical energy of the sound waves is effectively converted into heat energy in the process, and the sound waves can be effectively absorbed by the aerated concrete. The absorption and weakening of sound waves are realized, so that a remarkable sound absorption effect is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerated concrete blocks, in particular to a lightweight sound-insulating aerated concrete block and a preparation method thereof. Background Art

[0002] With the rapid development of modern society, the process of urbanization is accelerating, and the resulting environmental noise pollution problem is becoming increasingly prominent. These noise sources mainly include traffic vehicles, commercial activities, pedestrian noise, factory equipment operation and construction, etc. They affect people's daily lives all the time, interfere with normal rest, study and work, and may even cause a series of health problems. Therefore, the sound insulation performance of buildings has gradually become an important consideration for people when choosing a living or working environment.

[0003] In this context, soundproof aerated concrete blocks came into being and quickly gained wide application in the construction field. Soundproof aerated concrete blocks, also known as ALC (Autoclaved Lightweight Concrete) aerated concrete blocks or aerated concrete wall panels, are a lightweight building material with a porous structure. It is made by adding an appropriate amount of gas-forming agent (such as aluminum powder) to concrete and undergoing a series of processes such as batching, mixing, pouring, pre-curing, cutting, autoclaving and curing. This unique production process forms a large number of uniform and fine pores inside the blocks, giving them excellent sound insulation performance.

[0004] The sound insulation principle of soundproof aerated concrete blocks is mainly based on the absorption and dispersion of sound by their porous structure. The existing technology usually adds certain fibers to enhance its sound absorption capacity. However, since the added fibers are not treated, they are prone to aging and are not easy to disperse after addition, resulting in a decrease in its sound absorption capacity. Summary of the invention

[0005] The object of the present invention is to provide a lightweight sound-insulating aerated concrete block and a preparation method thereof, so as to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A lightweight sound-insulating aerated concrete block comprises, by mass fraction, 18-22 parts of cement, 52-56 parts of fly ash, 20-24 parts of lime, 2.6-3 parts of gypsum, 0.075%-0.085% of aluminum paste and 0.2%-0.3% of modified polypropylene fiber, and a water-to-material ratio of 0.58-0.61.

[0008] As an optimization, the modified polypropylene fiber is surface-modified by using diethylenetriaminopropylmethyldimethoxysilane, and the anti-aging agent and nano titanium dioxide are linked by diethylenetriaminopropylmethyldimethoxysilane.

[0009] As an optimization, the anti-aging agent is prepared by using cyanuric chloride as a core to graft 2-imidazolidinone and 2,4-dihydroxybenzophenone.

[0010] A method for preparing a lightweight sound-insulating aerated concrete block comprises the following steps:

[0011] S1. Add butyl titanate in anhydrous ethanol at a rate of 1 mL / s in an amount of 0.32 to 0.35 times the mass of anhydrous ethanol, stir for 10 to 15 minutes after the addition is complete, mix evenly, and obtain a butyl titanate solution; add the butyl titanate solution to a hydrochloric acid alcohol solution in an amount of 1.3 to 1.5 times the mass of the butyl titanate solution at a rate of 1 mL / s, stir evenly, and stir for 4.5 to 5.5 hours at a temperature of 35 to 45° C. to obtain a nano titanium dioxide sol;

[0012] S2. Deionized water, anhydrous ethanol and diethylenetriaminopropylmethyldimethoxysilane are weighed in a mass ratio of 1:8.7-8.9:0.055-0.06, and mixed evenly to prepare a diethylenetriaminopropylmethyldimethoxysilane solution; the pretreated polypropylene fiber is immersed in the diethylenetriaminopropylmethyldimethoxysilane solution, and the fiber is taken out after standing for 30-40 minutes, washed with deionized water for 2-3 times, and dried at a temperature of 95-100° C. for 2-3 hours to obtain a silane-grafted polypropylene fiber;

[0013] S3, adding the silane-grafted polypropylene fiber to acetone in an amount of 10 to 12 times the mass of the silane-grafted polypropylene fiber, and then adding an anti-aging agent in an amount of 0.25% to 0.28% times the mass of the silane-grafted polypropylene fiber, stirring evenly, adding a hydrochloric acid solution in an amount of 10 to 15% by mass to adjust the pH to 4 to 5, then heating to 105 to 115° C., reacting until the pH is constant, taking out the silane-grafted polypropylene fiber after the reaction, washing it repeatedly with acetone for 3 to 5 times, placing it at a temperature of 95 to 100° C., and drying it to constant weight to obtain anti-aging polypropylene fiber;

[0014] S4, adding the anti-aging polypropylene fiber to the nano titanium dioxide sol with a mass of 12 to 15 times of the anti-aging polypropylene fiber, stirring with ultrasonic for 15 to 20 minutes, stirring for 2 to 2.5 hours at a temperature of 75 to 85° C., taking out the anti-aging polypropylene fiber after the reaction, washing it with anhydrous ethanol for 2 to 3 times, and drying it to constant weight at a temperature of 95 to 100° C. to obtain modified polypropylene fiber;

[0015] S5. Weigh cement, fly ash, lime, gypsum and modified polypropylene fiber in a mass ratio of 18-22: 52-56: 20-24: 2.6-3: 0.075%-0.085%: 0.2%-0.3%, mix well, then add deionized water 2.4-2.8 times the mass of cement, stir for 3-4 minutes, add aluminum powder paste suspension 0.4-0.6 times the mass of cement, continue stirring for 0.5-1 minute to obtain slurry; pour the slurry into a mold, let it stand for 10-12 hours at a temperature of 45-55°C after pouring; after standing, steam cure at normal pressure for 22-26 hours.

[0016] As an optimization, the hydrochloric acid alcohol solution in S1 is prepared by uniformly mixing a hydrochloric acid solution with a mass fraction of 10 to 15% and anhydrous ethanol in a mass ratio of 1:4 to 5.

[0017] As an optimization, the pretreatment in S2 includes the following steps: the polypropylene fiber is soaked in anhydrous ethanol for 12 to 14 hours, then taken out, washed with deionized water for 2 to 3 times, and dried to constant weight at a temperature of 95 to 100° C. to complete the pretreatment.

[0018] As an optimization, the anti-aging agent in S3 includes the following preparation steps: at a temperature of 0 to 5° C., adding cyanuric chloride to acetone with a mass of 8.2 to 8.4 times that of cyanuric chloride, stirring for 20 to 25 minutes to mix evenly, then adding 2-imidazole 1.2 to 1.4 times the mass of cyanuric chloride, reacting for 2 to 2.5 hours, heating to 10 to 15° C., and then using a 15% mass fraction of sodium hydroxide solution to adjust the pH to 5.5 to 6, after the adjustment, adding 2,4-dihydroxybenzophenone solution with a mass of 0.85 to 0.9 times that of cyanuric chloride, heating to 40 to 45° C., reacting until the pH is constant, reducing pressure and filtering, and after the filtered product is repeatedly washed with acetone 2 to 3 times, the filter cake is placed in a vacuum drying oven to dry, and the anti-aging agent is obtained.

[0019] As an optimization, the aluminum powder paste suspension in S5 includes the following preparation steps: after heating the deionized water to 45-55° C., adding 0.0075%-0.0085% times the mass of the deionized water to the aluminum powder paste, stirring evenly, and preparing the aluminum powder paste suspension for use.

[0020] As an optimization, when pouring the slurry into the mold in S5, the pouring depth is 0.6 to 0.7 of the mold height.

[0021] As an optimization, the 2,4-dihydroxybenzophenone solution is prepared by adding 2,4-dihydroxybenzophenone to N,N-dimethylformamide with a mass of 4.3 to 4.7 times that of 2,4-dihydroxybenzophenone and stirring evenly.

[0022] A CVD coating suitable for a microporous wire drawing die is prepared by using any of the above preparation methods.

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0024] The present application not only significantly improves the overall performance of concrete, but also gives concrete new acoustic properties by incorporating polypropylene fibers into aerated concrete at a low dosage. The polypropylene fibers, with their unique physical properties and distribution, form a structure similar to natural or artificial fabrics in the pore network of aerated concrete. When sound waves pass through, they can induce tiny vibrations of the fibers, which then interact with the surrounding pore walls, including friction and energy conversion. This process effectively converts the mechanical energy of the sound waves into heat energy, achieving absorption and attenuation of the sound waves, thereby showing a significant sound absorption effect.

[0025] In addition, in order to solve the problems of poor bonding performance, easy agglomeration and poor anti-aging performance of polypropylene fibers in cement matrix, the present application firstly adopts silane coupling agent for surface modification treatment. As an important surface modifier, one end of the silane coupling agent in its molecular structure can chemically bond with the hydrophobic surface of the polypropylene fiber, and the other end can form a strong interaction with the hydrophilic component in the cement mortar. Through this modification, the surface of the polypropylene fiber is transformed from the original smooth state to a rough surface with a certain hydrophilicity, which significantly improves its dispersibility in the cement mortar and the bonding strength with the matrix, thereby effectively avoiding the fiber agglomeration phenomenon and ensuring the stability of the cement mortar performance.

[0026] Secondly, in order to solve the problems of thermal oxidation aging and photooxidation aging caused by unstable tertiary carbon atoms on the molecular chain of polypropylene fibers, the present application designs a highly efficient anti-aging agent, which uses cyanuric chloride as the core, externally connected to 2-imidazolidinone and 2,4-dihydroxybenzophenone, and is combined with diethylenetriaminepropylmethyldimethoxysilane and the last chlorine atom on cyanuric chloride, so that the anti-aging agent is directly linked to the polypropylene fiber, thereby significantly enhancing the antioxidant capacity of the polypropylene fiber and slowing down its aging speed in aerobic and light environments;

[0027] In order to further improve the anti-aging performance of polypropylene fiber, the present application also adopts the sol-gel method to prepare nano titanium dioxide, and uses diethylenetriaminepropylmethyldimethoxysilane to form a protective layer on the surface of polypropylene fiber. This protective layer not only enhances the bonding force between the fiber and the cement matrix, but also induces nano titanium dioxide to self-assemble on the fiber surface to form a dense shielding layer. This shielding layer is like an invisible armor, which effectively blocks the invasion of harmful factors such as oxygen and ultraviolet rays, and further prolongs the service life of polypropylene fiber. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] S1. Add butyl titanate in anhydrous ethanol at a rate of 1 mL / s in an amount of 0.32 times the mass of anhydrous ethanol, stir for 10 min after the addition is complete, mix evenly, and obtain a butyl titanate solution; add the butyl titanate solution to a hydrochloric acid alcohol solution in an amount of 1.3 times the mass of the butyl titanate solution at a rate of 1 mL / s, stir evenly, and stir for 4.5 h at a temperature of 35°C to obtain a nano-titanium dioxide sol; the hydrochloric acid alcohol solution is prepared by mixing a 10% mass fraction of hydrochloric acid solution and anhydrous ethanol in a mass ratio of 1:4;

[0031] S2. Deionized water, anhydrous ethanol and diethylenetriaminopropylmethyldimethoxysilane are weighed in a mass ratio of 1:8.7:0.055, and mixed evenly to prepare a diethylenetriaminopropylmethyldimethoxysilane solution; the polypropylene fiber is soaked in anhydrous ethanol for 12 hours, taken out, washed twice with deionized water, dried to constant weight at 95°C, and then immersed in the diethylenetriaminopropylmethyldimethoxysilane solution, left to stand for 30 minutes, taken out, washed twice with deionized water, and dried at 95°C for 2 hours to obtain silane-grafted polypropylene fiber;

[0032] S3, at a temperature of 0°C, add cyanuric chloride to acetone with a mass of 8.2 times that of cyanuric chloride, stir for 20 minutes to mix evenly, then add 2-imidazole 1.2 times the mass of cyanuric chloride, react for 2 hours, heat to 10°C, and then use a 15% sodium hydroxide solution to adjust the pH to 5.5. After the adjustment, add 2,4-dihydroxybenzophenone solution with a mass of 0.85 times that of cyanuric chloride, heat to 40°C, react until the pH is constant, reduce pressure and filter, wash the filtered product with acetone repeatedly twice, and place the filter cake in a vacuum drying oven to dry to obtain an anti-aging agent; 2,4-dihydroxybenzophenone solution is prepared by adding 2,4-dihydroxybenzophenone to N,N-dimethylformamide with a mass of 4.3 times that of 2,4-dihydroxybenzophenone, stirring evenly;

[0033] S4, adding the silane-grafted polypropylene fiber to acetone 10 times the mass of the silane-grafted polypropylene fiber, and then adding an anti-aging agent 0.25% times the mass of the silane-grafted polypropylene fiber, stirring evenly, adding a 10% mass fraction of hydrochloric acid solution to adjust the pH to 4, then heating to 105°C, reacting until the pH is constant, taking out the silane-grafted polypropylene fiber after the reaction, washing it repeatedly with acetone for 3 times, placing it at a temperature of 95°C, and drying it to constant weight to obtain anti-aging polypropylene fiber;

[0034] S5. Add the anti-aging polypropylene fiber into nano titanium dioxide sol with a mass 12 times of the anti-aging polypropylene fiber, stir it ultrasonically for 15 minutes, and then stir it for 2 hours at a temperature of 75°C. Take out the anti-aging polypropylene fiber after the reaction, wash it twice with anhydrous ethanol, and dry it to constant weight at a temperature of 95°C to obtain modified polypropylene fiber.

[0035] Example 2

[0036] S1. Add butyl titanate in anhydrous ethanol at a rate of 1 mL / s with a mass of 0.33 times that of the anhydrous ethanol, stir for 12 minutes after the addition is complete, mix evenly, and obtain a butyl titanate solution; add the butyl titanate solution to a hydrochloric acid alcohol solution in an amount of 1.4 times that of the butyl titanate solution at a rate of 1 mL / s, stir evenly, and stir for 5 hours at a temperature of 40°C to obtain a nano-titanium dioxide sol; the hydrochloric acid alcohol solution is prepared by mixing a hydrochloric acid solution with a mass fraction of 12% and anhydrous ethanol in a mass ratio of 1:4.5;

[0037] S2. Deionized water, anhydrous ethanol and diethylenetriaminopropylmethyldimethoxysilane are weighed in a mass ratio of 1:8.8:0.058, and mixed evenly to prepare a diethylenetriaminopropylmethyldimethoxysilane solution; the polypropylene fiber is soaked in anhydrous ethanol for 13 hours, taken out, washed twice with deionized water, dried to constant weight at 95°C, and then immersed in the diethylenetriaminopropylmethyldimethoxysilane solution, left to stand for 35 minutes, taken out, washed twice with deionized water, and dried at 95°C for 2.5 hours to obtain silane-grafted polypropylene fiber;

[0038] S3, at a temperature of 3 ° C, add cyanuric chloride to acetone 8.3 times the mass of cyanuric chloride, stir for 23 minutes to mix evenly, then add 2-imidazole 1.3 times the mass of cyanuric chloride, react for 2 to 2.5 hours, heat to 12 ° C, and then use a 15% sodium hydroxide solution to adjust the pH to 5.8, add 2,4-dihydroxybenzophenone solution 0.88 times the mass of cyanuric chloride after adjustment, heat to 43 ° C, react until the pH is constant, reduce pressure and filter, wash the filtered product with acetone repeatedly twice, and place the filter cake in a vacuum drying oven to dry to obtain an anti-aging agent; 2,4-dihydroxybenzophenone solution is prepared by adding 2,4-dihydroxybenzophenone to N,N-dimethylformamide 4.4 times the mass of 2,4-dihydroxybenzophenone, stirring evenly;

[0039] S4, adding the silane-grafted polypropylene fiber to acetone 11 times the mass of the silane-grafted polypropylene fiber, and then adding an anti-aging agent 0.27% times the mass of the silane-grafted polypropylene fiber, stirring evenly, adding a 12% mass fraction of hydrochloric acid solution to adjust the pH to 4.5, then heating to 110°C, reacting until the pH is constant, taking out the silane-grafted polypropylene fiber after the reaction, washing it repeatedly with acetone 4 times, placing it at a temperature of 98°C, and drying it to constant weight to obtain anti-aging polypropylene fiber;

[0040] S5. Add the anti-aging polypropylene fiber into nano titanium dioxide sol with a mass 13 times of the anti-aging polypropylene fiber, stir it ultrasonically for 18 minutes, and then stir it for 2 hours at 80°C. Take out the anti-aging polypropylene fiber after the reaction, wash it twice with anhydrous ethanol, and dry it to constant weight at 95°C to obtain modified polypropylene fiber.

[0041] Example 3

[0042] S1. Add butyl titanate in anhydrous ethanol at a rate of 1 mL / s in an amount of 0.35 times the mass of anhydrous ethanol, stir for 15 minutes after the addition is complete, mix evenly, and obtain a butyl titanate solution; add the butyl titanate solution to a hydrochloric acid alcohol solution in an amount of 1.5 times the mass of the butyl titanate solution at a rate of 1 mL / s, stir evenly, and stir for 5.5 hours at a temperature of 45°C to obtain a nano-titanium dioxide sol; the hydrochloric acid alcohol solution is prepared by mixing a hydrochloric acid solution with a mass fraction of 15% and anhydrous ethanol in a mass ratio of 1:5;

[0043] S2. Deionized water, anhydrous ethanol and diethylenetriaminopropylmethyldimethoxysilane were weighed in a mass ratio of 1:8.9:0.06, and mixed evenly to prepare a diethylenetriaminopropylmethyldimethoxysilane solution; the polypropylene fiber was soaked in anhydrous ethanol for 14 hours, taken out, washed with deionized water for 3 times, dried to constant weight at 100°C, and then immersed in the diethylenetriaminopropylmethyldimethoxysilane solution, allowed to stand for 40 minutes, taken out, washed with deionized water for 3 times, and dried at 100°C for 3 hours to obtain silane-grafted polypropylene fiber;

[0044] S3, at a temperature of 5 ° C, add cyanuric chloride to acetone with a mass of 8.4 times that of cyanuric chloride, stir for 25 minutes to mix evenly, then add 2-imidazole 1.4 times the mass of cyanuric chloride, react for 2.5 hours, heat to 15 ° C, and then use a 15% sodium hydroxide solution to adjust the pH to 6, after the adjustment, add 2,4-dihydroxybenzophenone solution with a mass of 0.9 times that of cyanuric chloride, heat to 45 ° C, react until the pH is constant, reduce pressure and filter, wash the filtered product with acetone repeatedly for 3 times, and place the filter cake in a vacuum drying oven to dry to obtain an anti-aging agent; 2,4-dihydroxybenzophenone solution is prepared by adding 2,4-dihydroxybenzophenone to N,N-dimethylformamide with a mass of 4.7 times that of 2,4-dihydroxybenzophenone, stirring evenly;

[0045] S4, adding the silane-grafted polypropylene fiber to acetone 12 times the mass of the silane-grafted polypropylene fiber, and then adding an anti-aging agent 0.28% times the mass of the silane-grafted polypropylene fiber, stirring evenly, adding a 15% mass fraction of hydrochloric acid solution to adjust the pH to 5, then heating to 115°C, reacting until the pH is constant, taking out the silane-grafted polypropylene fiber after the reaction, washing it repeatedly with acetone 5 times, placing it at a temperature of 100°C, and drying it to constant weight to obtain anti-aging polypropylene fiber;

[0046] S5. Add the anti-aging polypropylene fiber into nano titanium dioxide sol with a mass 15 times that of the anti-aging polypropylene fiber, stir it ultrasonically for 20 minutes, and then stir it for 2.5 hours at 85°C. Take out the anti-aging polypropylene fiber after the reaction, wash it with anhydrous ethanol for 3 times, and dry it to constant weight at 100°C to obtain modified polypropylene fiber.

[0047] Test Example 1

[0048] The modified polypropylene fibers prepared in Examples 1 to 3, the silane-grafted polypropylene fibers prepared in Example 2, the anti-aging polypropylene fibers and the polypropylene fibers were used to prepare lightweight sound-insulating aerated concrete blocks according to the following steps;

[0049] Cement, fly ash, lime, gypsum and modified polypropylene fiber were weighed in a mass ratio of 20:54:22:2.8:0.08%:0.25%, mixed evenly, and then deionized water 2.6 times the mass of cement was added, stirred for 3 minutes, and then aluminum powder paste suspension 0.5 times the mass of cement was added, and continued to stir for 1 minute to obtain slurry; the slurry was poured into a mold, and after pouring, it was allowed to stand for 12 hours at a temperature of 50°C; after standing, it was cured with normal pressure steam for 24 hours; when the slurry was poured into the mold, the pouring depth was 0.65 of the mold height;

[0050] Referring to the measurement standard of sound absorption coefficient and acoustic impedance in acoustic impedance tube GB / T 18696.1-2004, the sound absorption coefficient of the sound absorbing material was measured using the standing wave tube method.

[0051] Table 1 Sound absorption coefficient

[0052]

[0053] From the comparison of experimental data in Table 1, it can be found that the ASAC and NRC of aerated concrete in No. 1 to 5 remain stable, because the polypropylene fibers in several groups of experiments are not unevenly dispersed, and the sound absorption of concrete mainly relies on the dispersed polypropylene fibers to absorb the energy of sound propagation and reduce noise. Therefore, the sound absorption effect of aerated concrete in No. 1 to 5 is good.

[0054] In experiment No. 4, it is obvious that the experimental data of this group has declined significantly. The main reason is that the unmodified polypropylene fiber is not easy to disperse during the mixing process, and the uneven dispersion in the concrete leads to poor final sound absorption effect.

[0055] Test Example 2

[0056] The modified polypropylene fibers prepared in Examples 1 to 3, the silane-grafted polypropylene fibers, the anti-aging polypropylene fibers and the polypropylene fibers prepared in Example 2 were subjected to aging treatment in advance and then prepared and tested according to the steps in the above-mentioned Test Example 1;

[0057] The aging treatment uses a xenon lamp to simulate the entire spectrum of sunlight. The polypropylene fiber is placed in a xenon lamp accelerated aging test chamber. The aging time is 360 hours. The experimental conditions are air atmosphere, temperature 65°C, the light source is 25 cm away from the sample, and the radiation intensity is 550 W / m 2 ;

[0058] Table 2 Sound absorption coefficient after aging

[0059]

[0060] From the comparison of experimental data in Table 1, it can be found that the ASAC and NRC of aerated concrete in No. 1 to 3 remain stable, indicating that aging has little effect on the modified polypropylene fiber;

[0061] However, the rapid decline in No. 4 is mainly due to the fact that the anti-aging agent is not grafted, and its anti-aging performance is poor; the decline in No. 5 is relatively gentle, indicating that the grafted anti-aging agent plays an anti-aging role, and the decline in Example 6 is not obvious. It is speculated that although the aging effect occurs and the polypropylene fiber is greatly damaged, its sound absorption effect is not closely related to the polypropylene fiber due to its uneven dispersion in the above preparation process. It mainly depends on the performance of the aerated concrete itself, which leads to the slow decline in the final result.

[0062] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A lightweight sound-insulating aerated concrete block, characterized in that: Calculated by mass, it includes 18-22 parts of cement, 52-56 parts of fly ash, 20-24 parts of lime, 2.6-3 parts of gypsum, 0.075%-0.085% of aluminum paste and 0.2%-0.3% of modified polypropylene fiber, and the water-to-material ratio is 0.58-0.

61.

2. The lightweight sound-insulating aerated concrete block according to claim 1, characterized in that: The modified polypropylene fiber is surface-modified by using diethylenetriaminepropylmethyldimethoxysilane, and the anti-aging agent and nano titanium dioxide are linked by using diethylenetriaminepropylmethyldimethoxysilane.

3. The lightweight sound-insulating aerated concrete block according to claim 1, characterized in that: The anti-aging agent is prepared by taking cyanuric chloride as a core and grafting 2-imidazolidinone and 2,4-dihydroxybenzophenone.

4. A method for preparing a lightweight sound-insulating aerated concrete block, characterized in that: The following steps are involved: S1. Add butyl titanate in anhydrous ethanol at a rate of 1 mL / s in an amount of 0.32 to 0.35 times the mass of anhydrous ethanol, stir for 10 to 15 minutes after the addition is complete, mix evenly, and obtain a butyl titanate solution; add the butyl titanate solution to a hydrochloric acid alcohol solution in an amount of 1.3 to 1.5 times the mass of the butyl titanate solution at a rate of 1 mL / s, stir evenly, and stir for 4.5 to 5.5 hours at a temperature of 35 to 45° C. to obtain a nano titanium dioxide sol; S2. Deionized water, anhydrous ethanol and diethylenetriaminopropylmethyldimethoxysilane are weighed in a mass ratio of 1:8.7-8.9:0.055-0.06, and mixed evenly to prepare a diethylenetriaminopropylmethyldimethoxysilane solution; the pretreated polypropylene fiber is immersed in the diethylenetriaminopropylmethyldimethoxysilane solution, and the fiber is taken out after standing for 30-40 minutes, washed with deionized water for 2-3 times, and dried at a temperature of 95-100° C. for 2-3 hours to obtain a silane-grafted polypropylene fiber; S3, adding the silane-grafted polypropylene fiber to acetone in an amount of 10 to 12 times the mass of the silane-grafted polypropylene fiber, and then adding an anti-aging agent in an amount of 0.25% to 0.28% times the mass of the silane-grafted polypropylene fiber, stirring evenly, adding a hydrochloric acid solution in an amount of 10 to 15% by mass to adjust the pH to 4 to 5, then heating to 105 to 115° C., reacting until the pH is constant, taking out the silane-grafted polypropylene fiber after the reaction, washing it repeatedly with acetone for 3 to 5 times, placing it at a temperature of 95 to 100° C., and drying it to constant weight to obtain anti-aging polypropylene fiber; S4, adding the anti-aging polypropylene fiber to the nano titanium dioxide sol with a mass of 12 to 15 times of the anti-aging polypropylene fiber, stirring with ultrasonic for 15 to 20 minutes, stirring for 2 to 2.5 hours at a temperature of 75 to 85° C., taking out the anti-aging polypropylene fiber after the reaction, washing it with anhydrous ethanol for 2 to 3 times, and drying it to constant weight at a temperature of 95 to 100° C. to obtain modified polypropylene fiber; S5. Weigh cement, fly ash, lime, gypsum and modified polypropylene fiber in a mass ratio of 18-22: 52-56: 20-24: 2.6-3: 0.075%-0.085%: 0.2%-0.3%, mix well, then add deionized water 2.4-2.8 times the mass of cement, stir for 3-4 minutes, add aluminum powder paste suspension 0.4-0.6 times the mass of cement, continue stirring for 0.5-1 minute to obtain slurry; pour the slurry into a mold, let it stand for 10-12 hours at a temperature of 45-55°C after pouring; after standing, steam cure at normal pressure for 22-26 hours.

5. The method for preparing a lightweight sound-insulating aerated concrete block according to claim 4, characterized in that: The hydrochloric acid alcohol solution in S1 is prepared by uniformly mixing a hydrochloric acid solution with a mass fraction of 10 to 15% and anhydrous ethanol in a mass ratio of 1:4 to 5.

6. The method for preparing a lightweight sound-insulating aerated concrete block according to claim 4, characterized in that: The pretreatment in S2 comprises the following steps: soaking the polypropylene fiber in anhydrous ethanol for 12 to 14 hours, taking it out, washing it with deionized water for 2 to 3 times, and drying it at a temperature of 95 to 100° C. to a constant weight to complete the pretreatment.

7. The method for preparing a lightweight sound-insulating aerated concrete block according to claim 4, characterized in that: The anti-aging agent in S3 comprises the following preparation steps: adding cyanuric chloride to acetone with a mass of 8.2 to 8.4 times the mass of cyanuric chloride at a temperature of 0 to 5°C, stirring for 20 to 25 minutes to mix evenly, then adding 2-imidazole 1.2 to 1.4 times the mass of cyanuric chloride, reacting for 2 to 2.5 hours, heating to 10 to 15°C, and adjusting the pH to 5.5 to 6 with a sodium hydroxide solution with a mass fraction of 15%, adding 2,4-dihydroxybenzophenone solution with a mass of 0.85 to 0.9 times the mass of cyanuric chloride after adjustment, heating to 40 to 45°C, reacting until the pH is constant, filtering under reduced pressure, repeatedly washing the filtered product with acetone for 2 to 3 times, and then placing the filter cake in a vacuum drying oven to dry to obtain the anti-aging agent.

8. The method for preparing a lightweight sound-insulating aerated concrete block according to claim 4, characterized in that: The aluminum powder paste suspension in S5 includes the following preparation steps: heating deionized water to 45-55° C., adding 0.0075%-0.0085% of aluminum powder paste by mass of deionized water, stirring evenly, and preparing an aluminum powder paste suspension for use.

9. The method for preparing a lightweight sound-insulating aerated concrete block according to claim 4, characterized in that: When the slurry is poured into the mold in S5, the pouring depth is 0.6 to 0.7 of the mold height.

10. The method for preparing a lightweight sound-insulating aerated concrete block according to claim 7, characterized in that: The 2,4-dihydroxybenzophenone solution is prepared by adding 2,4-dihydroxybenzophenone to N,N-dimethylformamide which is 4.3 to 4.7 times the mass of 2,4-dihydroxybenzophenone and stirring the mixture evenly.

Citation Information

Cited By

  • Aerated concrete applied to sound insulation and heat preservation of floor slab and preparation method of aerated concrete

    CN120774735A

  • Aerated concrete applied to floor sound insulation and heat preservation and a preparation method thereof

    CN120774735B